Bone weathering in an Atlantic environment: preliminary results of the Global Weathering Project in Spain - A.B. Marín-Arroyo; Borja González-Rabanal; Jose Luís Arteche; Pilar Fatás; Manuel R. González Morales (Quaternary Science Advances, 2023)
Weathering constitutes one of the most investigated taphonomic processes for understanding the formation of archaeological and palaeontological assemblages. Despite being studied for decades through numerous monitoring experiments, no homogeneous methodology exists to compare the results obtained in different regions and climates. Here, we present the protocols and the preliminary results of an experimental research started four years ago in a coastal and inland location within the Cantabrian Region (northern Spain) to assess the influence of the weathering process in an Atlantic climate. This experiment allows evaluation of the preservation of faunal assemblages in regional open-air sites throughout the Middle and Upper Palaeolithic. We conduct this experiment within the Global Weathering Project of the International Council for Archaeozoologists (ICAZ), an international network of archaeozoologists and taphonomists who coordinates the same experiment worldwide. The experiment planned to last 18 years consists on recording the weathering stages suffered on the cow ribs disposed on the surface of a fenced enclosure under the protection of a cage, separated from the soil by a neutral inorganic substrate and close to a weather station where the temperature, humidity, rainfall, wind and sun exposure values are daily recorded.